Images of Socrates and Arastu in "Khamsa" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The epic poem "Khamsa" by one of the leading representatives of Uzbek and world classical literature, the great humanist poet Alisher Navoi, arose as a result of the fusion of the traditions of Eastern literature and the talent of the author. The great thinker in this work, based on his ideological and artistic concept, actively turned to many types of artistic creativity, poetic images and means of expression, depicting problems related to being, theology, society and man. One of them is the images of Greek scientists.In this article, related to the topic, the role of the images of Socrates and Aristotle, described in the epics of Navoi "Farhod and Shirin" and "Saddi Iskandariy", is analyzed, and their artistic and aesthetic functions in the plot and composition of these works, as characters in addition to the main characters, are analyzed. The article briefly outlines the ideas presented.